2021
DOI: 10.1038/s41419-021-03732-6
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of USP7 induces BCR-ABL degradation and chronic myelogenous leukemia cell apoptosis

Abstract: Chronic myelogenous leukemia (CML) is a clonal malignancy of hematopoietic stem cells featured with the fusion protein kinase BCR-ABL. To elicit the mechanism underlying BCR-ABL stability, we perform a screen against a panel of deubiquitinating enzymes (DUBs) and find that the ubiquitin-specific protease 7 (USP7) drastically stabilizes the BCR-ABL fusion protein. Further studies show that USP7 interacts with BCR-ABL and blocks its polyubiquitination and degradation. Moreover, USP7 knockdown triggers BCR-ABL de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 33 publications
0
30
0
Order By: Relevance
“…Recent studies have confirmed that BCR‐ABL can be degraded via the UPS, and several deubiquitinases have been reported to participate in this process. For instance, USP7 and USP25 cleave K48‐linkage poly‐ubiquitination conjugate from BCR‐ABL, which accelerates BCR‐ABL degradation through UPS 43,44 . In addition, inhibition of USP9X triggers K63‐linkage poly‐ubiquitination of BCR‐ABL, resulting in its accumulation in aggresomes 45 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have confirmed that BCR‐ABL can be degraded via the UPS, and several deubiquitinases have been reported to participate in this process. For instance, USP7 and USP25 cleave K48‐linkage poly‐ubiquitination conjugate from BCR‐ABL, which accelerates BCR‐ABL degradation through UPS 43,44 . In addition, inhibition of USP9X triggers K63‐linkage poly‐ubiquitination of BCR‐ABL, resulting in its accumulation in aggresomes 45 .…”
Section: Discussionmentioning
confidence: 99%
“…For instance, USP7 and USP25 cleave K48‐linkage poly‐ubiquitination conjugate from BCR‐ABL, which accelerates BCR‐ABL degradation through UPS. 43 , 44 In addition, inhibition of USP9X triggers K63‐linkage poly‐ubiquitination of BCR‐ABL, resulting in its accumulation in aggresomes. 45 It is still unknown whether USP14 or UCHL5 regulates the deubiquitination and subsequent degradation of BCR‐ABL protein.…”
Section: Discussionmentioning
confidence: 99%
“…Accumulated studies have also shown the apoptotic function of USP7 inhibition in a p53-independent manner. In chronic myelogenous leukemia (CML), USP7 is required for stabilization of BCR-ABL and activation of BCR-ABL signaling (83).Inhibiting USP7 was shown to cause BCR-ABL destabilization and to trigger apoptotic signaling pathways (83). In CLL cells, USP7 inhibition induces cell apoptosis by restoring nuclear localization of PTEN (84).…”
Section: Cell Apoptosismentioning
confidence: 99%
“…Phosphorylated USP7 gains increased deubiquitinating activity, thus promoting the nuclear exclusion of phosphatase and tensin homolog (PTEN), which disrupts PTEN’s tumor suppressive function in CML cells [ 32 , 33 ]. It is also demonstrated that USP7 interacts with BCR-ABL and blocks its polyubiquitination and degradation, thereby inhibiting its downstream signaling transduction [ 34 ]. Furthermore, USP7 is expressed mostly in the nucleus of normal CD34 + cells, but in primary CML CD34 + cells, it is expressed both in the nuclear bodies and cytoplasm [ 35 ].…”
Section: Introductionmentioning
confidence: 99%